Athletes' and Coaches' Attitudes Toward Protective Headgear as Concussion and Head Injury Prevention: A Scoping Review - Tjønndal, Anne; Austmo Wågan, Frida (Frontiers in Sports and Active Living, 2021)
The purpose of this article is to map existing research literature on athletes and coaches’ attitudes towards protective headgear in sport in relation to concussion and head injury prevention, and to identify and analyse knowledge gaps in the field. A scoping review was conducted in three databases; PubMed, Scopus, SportDiscus, and reference lists were searched to identify relevant grey literature. This process lead to an in-depth analysis of 18 peer-reviewed journal articles. Of the 18 studies identified, the majority focused on athletes (n=14), only two studies focused on coaches, and two studies included a sample of both athletes and coaches. The findings in this scoping review suggests that there is a discrepancy between attitudes and beliefs about the protective effects of headgear, athletes’ behaviour as far as wearing protective headgear, and coaches’ behaviour in terms of recommending use of protective headgear to their athletes. The majority of athletes in most of the reviewed literature believed that headgear had protective effects against concussion and other head injuries, however relatively few athletes report wearing this protective headgear unless it was mandatory by competition rules.